تحليل مشكلات ترجمة للطلاب المستوى السادس في فصل الترجمة شفوية - Mudlofir, Ali; Zahro, Ahmad; Rizkiyah, Mazidatur; Pangastuti, Nisa’ Setyaning Budi; Munifaturrohman, Raihanah (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
Translation provides a very positive contribution of knowledge to the world of education, namely translate the message or source language into the target language so that the readers or listeners can understand the message especially in the text. Translation from Arabic to Indonesian is dominated by religious texts such as the Al-Qur’an, hadith, aqidah, fiqh, morality, Sufism, education, da’wah, politics, philosophy, Islamic thought, language and literature, and history and stories. The problem of translating from Arabic to Indonesian often revolves around linguistic problems. Because of its urgency in the world of education, translation has become one of the subjects that must be studied by students. The translation course aims to equip students with knowledge of translation theory and to provide students with experience in translating various types of texts, such as religious, scientific, literary, economic, and cultural texts with varying degrees of difficulty.To achieve this goal, the author uses a qualitative approach and a descriptive approach and with data collection methods with documentation. The results showed that the problems that students often faced in translating were linguistic problems and the substantial differences between Arabic and Indonesian.